ANALISIS PENERAPAN AKUNTANSI FORENSIK DAN AUDIT INVESTIGATIF TERHADAP PENCEGAHAN DAN PENGUNGKAPAN FRAUD DALAM PENGELOLAAN KEUANGAN DAERAH PADA PERWAKILAN BPKP PROVINSI SULAWESI UTARA - Wuysang, Recky Vincent Oktaviano; Nangoi, Grace; Pontoh, Winston (Universitas Sam Ratulangi, 2016)
The purpose of this study is to explore and analyze: (1) the implementation of forensic accounting is applicable and effective functioning of the fraud prevention (preventive); (2) the implementation of forensic accounting is applicable and effective functioning of the fraud detection (detective); and (3) the implementation of investigative audit applicable and effective functioning of the fraud investigation (repressive) in the local ​​financial management. The analytical method used is descriptive qualitative methods that examines the participants perspective and some informations from the key informan through in-depth interviews and additional questions instrument by using purposive sampling, then make data triangulation obtained sources and collection techniques for analysis interactively by reducing, displaying in the form of a narrative texts, tables, matrix, charts, and then drawn a conclusion. The results of research and analysis states that forensic accounting is applicable and effective function to be applied to the fraud prevention (preventive) in the local financial management through the FCP, SPIP and SIMDA; forensic accounting is also applicable and effective function to be applied to the fraud detection (detective) in the local financial management through Operational Audit, Audit of Government goods and services Procurement (Probity Audit), EDP Audit: Computer Forensic, and Whistleblowers System; and the Audit Investigative very applicable and effective function to be applied to the fraud investigation (repressive) in the local financial management through investigative audits, in order to calculate losses of the state financial audits, and the provision of expert witness. Keywords : Fraud, Forensic Accounting, Investigative Audit, Local Financial Management.